Promoting Dairy Industry After the War- A Case Study of the Project of the SEED in the Vavuniya District - Mangaleswaran, T.; Jeyaseelan, G. (My University, 2010)
This paper investigates the performance of the community based project which was started in 2007 and implemented by the Social Economical and Environmental Developers (SEED) mainly in the areas of Sekkadipulavu and Rajendrakulam of the Vavuniya district during and after the war in Sri Lanka, especially of the dairy farmers on capacity building and transferring technical expertise to ensure a sustainable intervention. It studies the efficiency level of the implementing partner’s officials, livestock breeders’ cooperative society (Kamathenu), social mobilizers, the animal health workers (animators) and the beneficiaries, the problems encountered and the recommendations for the remedy. It assesses the participatory approach adopted to ensure a high degree of relevance and ownership, income generation activities of the farmers in the dairy sector by organizing them into dairy cooperatives in these locations. It further analyses the collection system efficiency, innovative ideas for economic improvement, cattle management practices, contribution to institutional development, women economic empowerment, contribution of service providers. A survey was conducted in July-August 2009 adopting methodological tools such as questionnaire, focus group discussion, interviews and the observations. The study concentrates on the satisfactory level of the outputs and outcomes of the project. They are less satisfactory in milk production to the expected level, milk collection, cattle management, milk based production, services provided (social mobilization, animation and collective participation), constant monitoring and intervention for sustainable development. The recommendations of this study would be helpful in the future dairy development projects, especially in monitoring the performance indicators in the successful outputs and outcomes of the project.